Handbook of layered materials edited by Scott M. Auerbach, Kathleen A. Carrado and Prabir K. Dutta. - Auerbach, Scott M.; Carrado, Kathleen A.; Dutta, Prabir K. (Marcel Dekker, 2004)
A collection of writings detailing experimental and theoretical methods for the study of microporous media and investigating specific features of the methodology of microporous media in comparison with traditional methods.